Social eating factors associated with energy intake in urban communities aged 25-45 years based on the Indonesian Food Barometer Study - Faradilla Nur Rahmah; Anna Fitriani; Fildzah Badzlina; Helda Khusun; Judhiastuty Februhartanty (Arsip Keilmuan Gizi (AKG), 2025)
Previous research indicates that individuals who engage in social eating tend to consume larger amounts of food and purchase foods with higher energy content than individuals who eat alone. This excess energy intake can lead to excess weight in a person, which can later have an impact on increasing the risk of developing various non-communicable diseases. Social eating factors found to influence energy intake include eating companions, activity while eating, and cooking practices. This study aims to analyze the relationship between social eating factors and energy intake. The methodology used is quantitative research with a cross-sectional study design and data analysis using the chi-square test. The research sample was taken based on the Indonesian Food Barometer (IFB) study using a probability sampling technique with a systematic random sampling type, which then obtained a sample of 450 subjects aged 25-45 years in urban areas of Indonesia. The results showed that 2.4% of subjects had an excess energy intake, 56% of subjects ate with others, 71.9% of subjects ate while doing other activities, and 54.9% of subjects had their food cooked by others. The statistical test results showed no significant relationship between social eating (eating companion, activity while eating, cooking practices) and energy intake (p values: 0.605; 0.996; 0.555, respectively). It can be concluded that social eating factors are not significantly related to energy intake in adult age groups in urban areas of Indonesia.